2017
DOI: 10.1177/0022034517698419
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Remineralization of Carious Lesions by Self-Assembling Peptide

Abstract: Caries is the most common disease in the world. Great efforts have been undertaken for prevention and to identify a regenerative treatment solution for dental caries. Self-assembling β-sheet forming peptides have previously shown to form 3-dimensional fiber networks supporting tissue regeneration. In particular, the self-assembling peptide P-4 has shown potential in the treatment and prevention of dental caries. It has previously been shown that application of monomeric P-4 solution to early carious lesions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 37 publications
6
130
0
2
Order By: Relevance
“…The greater difference between test and control lesions, however, occurred in the impedance values compared with that in the morphometric measurements, thereby confirming that SAP P 11 -4 acts predominantly by regenerating the mineral structure of the enamel of the lesion body and not just the surface 23,24 . Moreover, at the last study visit at day 180, the impedance values for test lesions indicated regression of caries into very outer enamel, whereas the impedance values for the control lesions indicated still caries throughout the whole enamel layer 31,33 , which agrees with previous data that fluoride (in the present study as fluoride-based professional prophylaxis paste and home care toothpaste) only acts in the top 30-50 µm of the enamel surface 13,14,34 .…”
Section: Discussionmentioning
confidence: 61%
“…The greater difference between test and control lesions, however, occurred in the impedance values compared with that in the morphometric measurements, thereby confirming that SAP P 11 -4 acts predominantly by regenerating the mineral structure of the enamel of the lesion body and not just the surface 23,24 . Moreover, at the last study visit at day 180, the impedance values for test lesions indicated regression of caries into very outer enamel, whereas the impedance values for the control lesions indicated still caries throughout the whole enamel layer 31,33 , which agrees with previous data that fluoride (in the present study as fluoride-based professional prophylaxis paste and home care toothpaste) only acts in the top 30-50 µm of the enamel surface 13,14,34 .…”
Section: Discussionmentioning
confidence: 61%
“…This rationally designed peptide self-assembles into hierarchical 3-dimensional fibrillar scaffolds in response to local conditions such as high ionic strength and acidic pH found in the lesion body [Kirkham et al, 2007]. The P11-4 fibrillar matrix has a high affinity for Ca 2+ ions and acts as a nucleator for de novo HA formation resulting in remineralization of the lesion body [Kind et al, 2017;Kirkham et al, 2007]. Analysis of in vitro data showed that the presence of P11-4 fibres in the lesion body resulted in faster HA formation, yielding tangentially arranged needle-shaped crystals, with increased microhardness of the remineralized subsurface lesion [Schmidlin et al, 2016;Sousa et al, 2017;Takahashi et al, 2016].…”
Section: Biomimetic Remineralizationmentioning
confidence: 99%
“…In addition to temperature and metal ligation (as with Biogelx) triggered gelation, the physicochemical properties of the supramolecular hydrogels can be tuned to achieve various desirable properties. For instance, the ability of PuraMatrix and Curodont is under consideration as fillers for dental lesions due to their ability to undergo biomineralization, which can be influenced by both chemistry and hydrophobicity of the precursors . In essence, temperature‐responsive supramolecular hydrogels that can undergo biomineralization could guide enamel regeneration through de novo mineralization and growth.…”
Section: Conclusion and Perspectivementioning
confidence: 99%